How is infection diagnostic criteria for shoulder periprosthetic joint infection reported in literature: systematic review - Alexis L. Clifford, BS; Eoghan Hurley, MB, BCh, MCh, PhD; Dana Rowe, BA; Lulla Kiwinda, BS; Tom R. Doyle, MB, MCh; Bryan S. Crook, MD; Grant E. Garrigues, MD; Jason E. Hsu, MD; Thorsten M. Seyler, MD, PhD; Oke A. Anakwenze, MD, MBA; Christopher S. Klifto, MD (JSES International)
Background: The purpose of this study was to elucidate which criteria are being reported in the literature for the workup and diagnosis of shoulder periprosthetic joint infection (PJI). Studies published prior to or after 2019 were compared to elucidate any changes secondary to the publication of shoulder-specific PJI criteria written by the International Consensus Meeting (ICM). Methods: Two independent reviewers performed the literature search on PubMed following Preferred Reporting Items for Systematic Reviews and Meta-Analysesguidelines. Studies of revision shoulder arthroplasty containing at least a subset of patients revised for infection were included. The infectious parameters utilized were extracted, including the use of 1) established guidelines or criteria from professional societies or consensus meetings, 2) laboratory indices, 3) clinical symptoms, 4) findings from biologic samples, and 5) imaging modalities. These studies were then categorized based upon where the study was conducted. Results: This review included 231 studies, 187 (81%) of which reported the criteria required for workup of PJI. 73 studies reported specifically on revision for infection, with 71 (97.3%) providing workup criteria. 137 (59.3%) of these studies were conducted in US hospitals, with 109 (79.5%) reporting infectious criteria. 83 (35.9%) were conducted in Europe, with 70 (84.3%) reporting criteria. Among these studies, 124 (53.7%) were published prior to 2019, with 80.6% reporting criteria and 11.3% reporting use of established criteria, such as Musculoskeletal Infection Society, ICM, Infectious Disease Society of America, or European Bone and Joint Infection Society. Of the 107 studies published in or after 2019, 81.3% published criteria and 52.3% reported established criteria. There increase in utilization of established criteria is echoed by 28.9% of studies published in or after 2019 having utilized ICM criteria. Conclusion: This systematic review demonstrates that the evaluation workup and criteria used to diagnose shoulder PJI remain inconsistent. While there has been an increase in the use of established criteria since the creation of ICM shoulder-specific criteria, further adoption is required to improve the strength of clinical research.